En bra plats för lek : kreativ och tillgänglig lekplats i Hedemora - Eriksson, Jenny (SLU/Dept. of Urban and Rural Development, 2008)
For an outdoor environment to function optimally as a playarea requires that it is flexible, that is, contains places and elements that give room for the imagination and for own interpetretations, and also that the children in some way can influence and change their surroundings. It is also important to have variety, both in the sense that the playground has a unique character that distinguishes it from other places, and that it allows many different games and activities. There should for example be room for both wild games of running and moving around where many children can participate, and calm corners to withdraw to for rest or quiet play.